Sagittal Abdominal Diameter does not Predict Metabolic Traits Better than Waist Circumference-Related Measures of Abdominal Obesity in Obese Subjects - Zazai, Runa; Wilms, Britta; Ernst, Barbara; Keppler, Rahel; Thurnheer, Martin; Schmid, Sebastian M.; Schultes, Bernd (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Recently, we showed that in subjects with a body mass index (BMI) >35 kg/m2 waist circumference (WC) is associated with metabolic traits but associations were weaker in men than in women.Aims To confirm our previous observation that anthropometric measures of abdominal obesity are closer linked to metabolic traits in obese women than obese men. To test whether sagittal abdominal diameter (SAD) provides a better prediction of metabolic traits in obese subjects than WC related measures.Methods SAD and WC along with metabolic traits were assessed in 204 women and 69 men (BMI 30.1–64.0 kg/m2).Results In women, abdominal obesity measures were associated with glycated hemoglobin levels (HbA1c), fasting serum glucose, insulin, triglycerides (TG), total cholesterol (Chol), high-density lipoprotein (HDL), and uric acid levels as well as Chol/HDL ratio and homeostatic model assessment of insulin resistance (HOMA-IR) independently of age and BMI. SAD predicted serum insulin and Chol better than WC, whereas WC was superior to SAD in predicting HbA1c, glucose, HOMA-IR, TG, HDL, Chol/HDL, and uric acid. Of note, the combination of SAD and WC provided a better prediction of insulin, HOMA-IR, TG, and uric acid than each of these anthropometric alone. In men, only fasting glucose, Chol, and uric acid levels were associated with abdominal obesity markers.Conclusion Data show various associations between anthropometric measures of abdominal obesity and metabolic traits in obese women but overall much less in obese men. Most metabolic traits are better predicted by WC than by SAD.
Keywords: waist circumference; sagittal abdominal diameter; glucose; lipids; uric acid; metabolic syndrome